A laboratory simulation of the effects of acute salinity decrease on osmoregulation and Hsps expression in the swimming crab, Portunus trituberculatus: implications for aquaculture - Lu, Yun Liang; Wang, Fang; Jia, Xu Ying; Gao, Qin Feng; Dong, Shuang Lin (Marine and freshwater behaviour and physiology, 2013)
Groups of swimming crabs, Portunus trituberculatus, were subject to sharp decreases of water salinity from 30 to 25, 20 and 15 psu, respectively, under laboratory conditions to simulate events that could occur during culture. Their osmoregulation and heat shock proteins (Hsps) expression were analysed. After the salinity stress, hemolymph osmolality, osmotic enzymes (Na + /K + -ATPase and carbonic anhydrase) activities in gills and Hsps (Hsp70 and Hsp90) expression in gills and muscles were measured. Dramatic changes in all parameters (p < 0.05) were detected after acute salinity decrease to 15 psu, while a decrease to 25 psu resulted in only slight changes except in the muscle Hsps levels. Hemolymph osmolalities in all treatments were significantly reduced after the salinity decrease (p < 0.05), and the greater the salinity change, the more the osmolality decrease. The osmotic enzymes activities and Hsps concentrations increased simultaneously after the salinity decrease. The osmotic enzymes activities were elevated at the end of the study with a significant difference at 15 psu but not at 25 psu compared with controls. The muscle Hsps levels were reduced in all treatments and the gill Hsps levels increased except that at 25 psu. It can be concluded that acute salinity decrease can have a negative impact on P. Trituberculatus but a salinity change of less than 10 psu is likely to be harmless for crab farming.